Geothermal Energy in Uganda, Country Update - Bahati, Godfrey; Natukunda, James Francis; Tuhumwire, Joshua (In International Geothermal Conference, Reykjavik, Iceland, 2003)
Exploration for geothermal energy in Uganda has been in progress since 1993. The studies have focused on three major geothermal areas namely Katwe, Buranga and Kibiro.The three areas are in advanced stages of surface exploration and will soon be subjected to exploratory drilling that will pave the way for a feasibility study. The overall objective of the study is to develop geothermal energy to complement hydro and other sources of power to meet the energy demand of rural areas in sound environment. The current study has focused on geology, geochemistry, hydrology and geophysics with the aim of elucidating subsurface temperatures and the spatial extent of the geothermal systems. The results indicate that the geothermal activity in the three areas is related to the volcanic and tectonic activities of the Rift Valley, which has a higher heat flow than the surrounding Precambrian crust. Subsurface temperatures of approximately 140-200˚C for Katwe, 120- 150˚C for Buranga, and 200-220˚C for Kibiro have been predicted by geothermometry and mixing models. Anomalous areas have been delineated in Katwe and Kibiro prospects using geophysical methods. Drilling of shallow boreholes to a depth of 200-300m for temperature gradient measurement has been completed and the temperatures measured (30-36˚C/km) are slightly above the global average of 30˚C/km, which suggests deep reservoirs in Katwe and Kibiro or geothermal reservoirs offset from the drilled areas. Additional geophysical measurements to locate the deep reservoirs and drill sites in the two areas are recommended. The results will then be used to update the geothermal models that will be a basis for the drilling of deep geothermal wells. The Buranga area still needs detailed geophysical surveys to delineate anomalous areas that could be targets for drilling. The results of the preliminary geothermal investigations on other areas predict subsurface temperatures of 100 - 160˚C suitable for small scale electricity production and direct uses. These areas have been ranked based on predicted subsurface temperatures and other geothermal features for further exploration and development.
Keywords: Uganda, geothermal, surface surveys, feasibility